Making Myths: Billy the Kid, George Armstrong Custer, Buffalo Bill, and the Media - Spicer, Veronica (URJ-UCCS: Undergraduate Research Journal at UCCS, 2013)
This paper examines how the media shaped the mythology of three notable historical figures: Billy the Kid, George Armstrong Custer, and Buffalo Bill. Through newspapers, paintings, or books, these men became legends. This paper seeks to understand how certain types of media and the public’s demand of certain images, ultimately impacted their legacies. Buffalo Bill manipulated the media to portray himself in a certain light, while Custer and Billy the Kid did not have as great of control over their personas. In the end, the media allowed these men to become American cultural icons. However, these myths pose a potential problem for the study of history: where does the fiction stop and the facts begin?